Understanding High School Students’ Errors in solving Mathematics Problems: A Phenomenological Research - Ahmad Naufal Aljura; Heri Retnawati; Hutkemri Zulnaidi; Vianney Mbazumutima (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
This research aims to understand a phenomenon regarding high school students’ errors in solving mathematics problems using a qualitative approach with phenomenology as the analysis framework. Data were collected through tests, classroom observations, documentation (students’ answer sheets, list of attendees, and students’ score lists), and unstructured phenomenological interviews with four purposively selected participants who met the selection criteria. The researchers used the mathematical problem-solving (MPS) model by Rott-Specht-Knipping and Aguas’ phenomenological data analysis steps using the NVIVO 12 software to analyze the students’ MPS process and identify their errors and the factors contributing to these errors. Errors were predominantly found in problems solved without engaging in the exploration phase. Analysis errors were the most common, while errors due to carelessness were the rarest. Factors contributing to these errors were identified across five domains: MPS Ability (MPSA), cognition, affection, motivation, and self-awareness. This research provides valuable insights into student errors in MPS for researchers and educators, particularly teachers, and provides recommendations for mathematics education policies and future research.